2016
DOI: 10.5539/enrr.v6n4p18
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antileishmanial Activity of Essential Oils of Native Species from Southern Brazil

Abstract: Leishmaniasis are a neglected tropical diseases that affecting 98 countries on three continents. Every year, 1.3 million of people are infected with the disease and 50.000 persons die because of this. The aim of this work was to evaluate antileishmanial activities in vitro from native species of South of Brazil belonging to the Myrtaceae family. The essential oils from leaves of Calyptranthes grandifolia, Calyptranthes tricona, Eugenia anomala, Eugenia arenosa, Eugenia pyriformis, Myrrhinium atropurpureum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Another study on promastigotes and amastigotes of L. amazonensis showed that the hydroalcoholic extract of P. guajava leaves at 100 µg /mL reduced growth by 65.4% and 52%, respectively [19]. Another species of the Psidium genus, P. salutare, showed a limited inhibition effect on the growth of promastigotes of L. amazonensis [20] Speci c metabolites such as kaempferol, a avonol found in different plants such as Brassica oleracea and Hamamelis virginiana, have shown to be effective against axenic amastigotes and amastigotes in macrophages of L. donovani [21]. Previous studies report the use of P. guajava in traditional medicine against leishmaniasis in local communities where the plant grows [22][23][24][25][26] Another study on the metabolites of P. guajava leaves against the axenic amastigotes and promastigotes of L. infantum showed parasite activity mainly in the apolar fractions, and the crude ethanolic extract at 25 µg/mL against axenic amastigotes inhibited 50% of the parasites in the crude extract and up to 80% in the apolar fractions as triterpenoids including jacumaric acid and corosolic acid, while, at 25 µg/mL and 50 µg/mL in promastigotes, no activity was observed in either the polar or apolar fractions [27].…”
Section: Resultsmentioning
confidence: 99%
“…Another study on promastigotes and amastigotes of L. amazonensis showed that the hydroalcoholic extract of P. guajava leaves at 100 µg /mL reduced growth by 65.4% and 52%, respectively [19]. Another species of the Psidium genus, P. salutare, showed a limited inhibition effect on the growth of promastigotes of L. amazonensis [20] Speci c metabolites such as kaempferol, a avonol found in different plants such as Brassica oleracea and Hamamelis virginiana, have shown to be effective against axenic amastigotes and amastigotes in macrophages of L. donovani [21]. Previous studies report the use of P. guajava in traditional medicine against leishmaniasis in local communities where the plant grows [22][23][24][25][26] Another study on the metabolites of P. guajava leaves against the axenic amastigotes and promastigotes of L. infantum showed parasite activity mainly in the apolar fractions, and the crude ethanolic extract at 25 µg/mL against axenic amastigotes inhibited 50% of the parasites in the crude extract and up to 80% in the apolar fractions as triterpenoids including jacumaric acid and corosolic acid, while, at 25 µg/mL and 50 µg/mL in promastigotes, no activity was observed in either the polar or apolar fractions [27].…”
Section: Resultsmentioning
confidence: 99%
“…19 Another species of the Psidium genus, P. salutare, showed a limited inhibition effect on the growth of promastigotes of L. amazonensis. 20 Specific metabolites such as kaempferol, a flavonol found in different plants such as Brassica oleracea and Hamamelis virginiana, have shown to be effective against axenic amastigotes and amastigotes in macrophages of L. donovani. 21 Previous studies report the use of P. guajava in traditional medicine against leishmaniasis in local communities where the plant grows.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in agreement with our findings which demonstrated a high amount of polyphenols in the aqueous extract of C. grandifolia. Since there are only few data concerning the chemical composition of C. grandifolia, our study is of importance and our identified molecules need to be added to the known molecules previously identified in this species which may help to elucidate some attributed biological activities such as neuromodulatory effects (Kich et al 2016) and potent antileishmanial actions (Kauffmann et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Since modulation of the immune system has been an emerging concept in the control of tumor cell proliferation, targeting protein kinases may be a useful strategy to generate antitumor drugs (Kauffmann et al 2016;Limberger et al 2002). In order to investigate the specificity of C. grandifolia as a kinase inhibitor, the aqueous extract was tested for its ability to inhibit JAK3 and p38α in vitro.…”
Section: Grandifolia Extract As a Potent Jak3 And P38α Kinase Inhibit...mentioning
confidence: 99%
See 1 more Smart Citation